MENGURAI ALASAN BERTAHANNYA PERNIKAHAN DINI DALAM MASYARAKAT KONTEMPORER - Dzakiyyah Nisrina Firdaus; Alfan Huda (Yayasan Literasi Sains Indonesia, 2026)
Technological advances accompanying contemporary society present a new paradox in adolescent dynamics. Access to information and education is increasingly widespread. However, digital openness has actually triggered an increase in risky behavior in adolescent sexual relationships. This phenomenon raises crucial questions about the factors that cause early marriage to persist in the midst of modernity. This study uses a Systematic Literature Review to explore academic studies on the relationship between technological developments, adolescent behavior, and the decision to marry early. The SLR procedure was carried out by formulating research questions, compiling keywords, searching for articles in reputable databases, and filtering. Articles that met the criteria were analyzed to identify research gaps. The results show that early marriage in modern society is driven by three main factors. First, the intensity of adolescent interaction through digital media increases the likelihood of sexual relationships. Second, there is a gap in social control, weak digital literacy, and minimal parental supervision. Third, families tend to use marriage as a quick solution to cover up moral consequences, thereby perpetuating this practice. These findings confirm that early marriage is not merely a cultural issue, but a contemporary problem triggered by changes in adolescent behavior in the digital ecosystem. This provides a deeper understanding of new analyses of interventions based on digital literacy, sex education, and strengthening social control.